(7x + 8)(7x - 9)
49x2 - 84x + 36 = (7x - 6)(7x - 6) or (7x - 6)2
It equals 53X- a number is squared when it is multiplied by itself, so 7X by 7X = 49X. 2X by 2X =4X, so 49X + 4X is 53X.
If you mean (4x+7)(7x+6) then it is 28x^2 +24x+49x+42 using the FOIL method
(-7x + 3)(-7x +3)
7x2+49x-42 = 7(x2+7x-6)
49x
It is a quadratic expression and it is (7x+6)(7x+6) when factored
49x.
7x2+49x+84 = 0 Divide all terms by 7: x2+7x+12 = 0 Factorize: (x+3)(x+4) = 0 Therefore the x intercepts are -3 and -4
Pi Ok, it really cannot be answered without knowing to what it is equal and to which form of the equation you are referring: (7x)^2 - 14x = 49x^2 - 14x =7(7x^2 - 2x) or 7(x^2) - 14x = 7(x^2 - 2x)
98x